Dysregulated peripheral proteome reveals NASH-specific signatures identifying patient subgroups with distinct liver biology - Stiglund, Natalie; Hagström, Hannes; Stål, Per; Cornillet, Martin; Björkström, Niklas K. (Frontiers in Immunology, 2023)
Background and aims: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease. The prognosis may vary from simple steatosis to more severe outcomes such as nonalcoholic steatohepatitis (NASH), liver cirrhosis, and hepatocellular carcinoma. The understanding of the biological processes leading to NASH is limited and non-invasive diagnostic tools are lacking. Methods: The peripheral immunoproteome in biopsy-proven NAFL (n=35) and NASH patients (n=35) compared to matched, normal-weight healthy controls (n=15) was studied using a proximity extension assay, combined with spatial and single cell hepatic transcriptome analysis. Results: We identified 13 inflammatory serum proteins that, independent of comorbidities and fibrosis stage, distinguished NASH from NAFL. Analysis of co-expression patterns and biological networks further revealed NASH-specific biological perturbations indicative of temporal dysregulation of IL-4/-13, -10, -18, and non-canonical NF-k signaling. Of the identified inflammatory serum proteins, IL-18 and EN-RAGE as well as ST1A1 mapped to hepatic macrophages and periportal hepatocytes, respectively, at the single cell level. The signature of inflammatory serum proteins further permitted identification of biologically distinct subgroups of NASH patients. Conclusions: NASH patients have a distinct inflammatory serum protein signature, which can be mapped to the liver parenchyma, disease pathogenesis, and identifies subgroups of NASH patients with altered liver biology.